Identity Research Desing: A Search for Identities of Generations in the Autobiographies of XXth Century Lithuanian - Kraniauskienė, Sigita (Sociologija. Mintis ir veiksmas, 2004)
Any empirical research of identity confronts a serious methodological issue. If social scientists categorise different human settings in society with assignment of certain social features as a base of collective identity, is it appropriate to talk about a certain identity as a really existing phenomenon at all? Our attempts to answer this question are based on the examination of specific character of a qualitative research of cohort generation identities in the XX century’s Lithuania. The article discuses a general meaning of identity concept and its connections with autobiographical narrative, defines concepts of collective and individual identity, theorises the process of social identity construction within social group and in the cases of social category, analyses dimensions of nominal and real identity. Discussion of social identity construction is based on the idea of Anselm Strauss that life story narratives involve both personal and collective / social history. Biographical processes refer not only to individual but also to collectivities. Individual experiences are very often shaped by similar events. Similar experiences are treated as a symbolic universe, in the words of P. Berger and Th. Luckmann. It is a realm of common values advanced and shared due socialization. This universe in biographies is expressed through individual perception and narration or, according to A. Strauss, through symbolic representations. Those representations are experiential perceptions of certain structural social and historical circumstances. Such premise allows us to treat autobiography as narrative, where individual representations of identity intermingle with a general structure of social identity through merge of personal feelings, common historical experience, and shared worldview. The common experiences consolidate humans into social units called cohort generations. Mentioned theoretical assumptions give us a good reason to search for a common identity of cohort generations in the individual biographies.Consequently, scientifically exploring identity of cohort generations, social scientists have to comprehend and focus on social categories and practices, which are empirically represented by the authors in autobiographies. It means that such point of view acknowledges a real appearance of identity and gives a nominal dimension to it.
Keywords: social identity; generation identity; autobiogrphical narrative